Accounting for Identity Theft: The Roles of Lifestyle and Enactment. (August 2013) - Copes, Heith; Vieraitis, Lynne M.; Cardwell, Stephanie M.; Vasquez, Arthur
White-collar offenders are thought to be particularly adept at excusing and justifying their crimes. Whether this is due to their personal backgrounds or the characteristics of their crimes is, as of yet, unknown. To shed light on this issue we explore the various justifications and excuses given by identity thieves. Using data from semistructured interviews with 49 federally convicted identity thieves we show that they all provided numerous accounts for their crimes, with denial of injury being the most common. We also find that the use of accounts varies by the lifestyles these offenders live. That is, those seeking to live as conventional citizens call forth different accounts than those who have a criminal lifestyle.